Pendampingan Metode An-Nashr Bagi Pendidik Sebagai Pengembangan Pembelajaran Al-Quran Di Madrasah Diniyah Raudhatul Jannah Malang: Assistance of the An-Nashr Method for Educators as a Development of Al-Quran Learning at Madrasah Diniyah Raudhatul Jannah Malang - A. Qomarudin; Amrullah, Zen (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The main focus of this scientific article is to identify the problems faced by educators in learning to translate the Quran, develop appropriate mentoring strategies, and evaluate the results of mentoring at Madrasah Diniyah Raudhatul Jannah Singosari Malang. The mentoring method uses  Participatory Action Research (PAR) with the following implementation stages: the process of inculturation and participatory mapping, the formulation of humanitarian problems, the formulation of strategic planning, the implementation of programs, and supervision and reflection. The results of the service show that educators face challenges in the development of Quranic learning that focuses on teaching Quranic translation, such as a lack of a deep understanding of Arabic and the limitations of the methods used. Therefore, a mentoring strategy is needed through training in the an-Nashr method which focuses on strengthening the skills of memorizing and translating the Quran with a pattern of repetition of 4,3,2,1. The results of the service show that the assistance of the An-Nashr Method significantly improves the ability of educators to teach the translation of the Quran through the 4-3-2-1 repetition pattern, so that learning becomes more effective and systematic